Note - The Control and Eradication of Invasive Species in Urban Areas in terms of South African Law: The City of Cape Town and the Polyphagous Shot Hole Borer Beetles - Salmons, Marcelle (Potchefstroom Electronic Law Journal, 2021)
The introduction and prevalence of invasive species is an alarming reality in South Africa. The emergence of invasive species has resulted in harmful consequences on various levels and has adverse impacts on the environment and the economy. Hence, biological invasions demand attention. The control and eradication of invasive species can serve to minimise their adverse impact. In 2019 the South African National Biodiversity Institute highlighted the threats posed by biological invasions in South Africa and specifically identified Polyphagous Shot Hole Borer Beetles as a significant new invasive species in South Africa that has a demonstrable ongoing detrimental impact on varieties of trees. Polyphagous Shot Hole Borer Beetles have been detected in various urban areas in South Africa, including the City of Cape Town. This note briefly examines the control and eradication of invasive species in urban areas in terms of the South African legal framework, specifically against the backdrop of the emergence of the Polyphagous Shot Hole Borer Beetles in the City of Cape Town.